2003
DOI: 10.1590/s0102-05362003000200016
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação técnica e econômica do espaçamento de gotejadores em tomateiro para processamento cultivado em fileiras simples e duplas

Abstract: O tomateiro para processamento in dustrial é a hortaliça de maior importância econômica cultivada na região do Cerrado do Brasil. Em 2001, a área cultivada nos estados de Goiás e Minas Gerais foi de 12,7 mil hectares, o que representa cerca de 80% da área brasileira. A cultura é quase que totalmente irrigada por aspersão, sendo o pivô central e o plantio em fileiras simples o sistema de produção mais empregado na região (Giordano et al., 2000;Silva et al., 2001a).Nos últimos anos, a utilização do pivô central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…These results are in agreement with Branco et al (2010) and Marouelli et al (2011a), who also found no variation in the productivity of the organic tomato whether irrigated by drip or sprinkler. This differs however from studies conducted in conventional production systems, where the yield of the tomato irrigated by drip is typically greater than when irrigated by sprinkler (HANSON, MAY, 2004;MAROUELLI et al, 2003). The reason for this difference may be exactly the fact that this study was carried out on an organic system.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…These results are in agreement with Branco et al (2010) and Marouelli et al (2011a), who also found no variation in the productivity of the organic tomato whether irrigated by drip or sprinkler. This differs however from studies conducted in conventional production systems, where the yield of the tomato irrigated by drip is typically greater than when irrigated by sprinkler (HANSON, MAY, 2004;MAROUELLI et al, 2003). The reason for this difference may be exactly the fact that this study was carried out on an organic system.…”
Section: Resultsmentioning
confidence: 71%
“…Similarly, marketable-fruit weight (average 150 g) was not affected by the irrigation or cultivation systems (Table 1). Marouelli et al (2003) and Marouelli et al (2011a) also found no significant effect of the different irrigation systems on the weight of the tomato fruit.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…There is also a fairly extensive literature in Brazil that seeks to determine the optimal type and level of irrigation for certain commercially important crops like processing tomatoes (Silva and Marouelli 1999;Marouelli et al 2003;Marouelli and Silva 2007). Marouelli and Silva (2007) explained that drip irrigation is superior to surface or deficit irrigation systems for processing tomatoes because it reduces water use by 30 percent while not adversely affecting yields.…”
Section: Effects Of Different Types Of Irrigation On Crop Yields Wate...mentioning
confidence: 99%